Model Organizational Citizenships Behavior Dalam Meningkatkan Kinerja Kepolisian : di Wilayah Hukum Polresta Mataram - Muhammad Gifari Syarifuddin; Ilham Prisgunanto; Jarot Prianggono (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
The police in carrying out their duties often have to deal with the community with various problems related to law enforcement and maintaining order so that it has an impact on social trust in the police. In order to build public trust, Polri needs to show its best performance in public service. Polri's performance will be influenced by many factors, one of which is organizational citizenship behavior. The purpose of this study was to determine the effect of the organizational citizenship behavior model on police performance. The theories and concepts used in this study are the concept of the Indonesian National Police, performance theory, social trust theory, organizational citizenship behavior, human capital theory, leader-member exchange theory, and organizational behavior theory. This research uses a quantitative approach with a research method that is observational analytic research. There were two groups of samples, namely 110 from members of the Mataram Police and 110 from community groups. The variables of this study are organizational factors, organizational citizenship behavior, Polri performance. Data collection techniques using a questionnaire. The first stage of analysis uses a structural model with PLS (Partial Least Square). From the results of this study it was found that the results of testing the outer model showed that this study had good convergent validity and the results of testing the inner model showed that each exogenous variable had a significant effect on the endogenous variables. The conclusion in this study is that there is an influence of organizational factors on organizational citizenship behavior, there is an influence of organizational citizenship behavior on Polri's performance. To increase public trust in the Police, the Police need to show performance that is in line with the expectations of the community.